2020
DOI: 10.1039/d0lc00605j
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary-arterial-hypertension (PAH)-on-a-chip: fabrication, validation and application

Abstract: Currently used animal and cellular models for pulmonary arterial hypertension (PAH) only partially recapitulate its pathophysiology in humans and are thus inadequate in reproducing the hallmarks of the disease, inconsistent...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 41 publications
0
42
0
Order By: Relevance
“…Economic use of cells, short experimental time, device scalability, low production and operation cost make it an attractive model for drug testing and a viable alternative to animal experimentation. The only other existing PAH-on-a-chip model 71 included intimal, medial and adventitial cells from PAH pulmonary arteries grown on polylysine-coated glass in straight channels arranged side-by-side, with cell-to-cell contact restricted to the gaps between silicone posts situated between the channels. This model can provide valuable information regarding paracrine regulation of cell migration (de ned as remodelling sic) but cannot evaluate endothelial barrier function and is limited by poor accessibility of patient lung material, which precludes its wider application in research and drug testing.…”
Section: Discussionmentioning
confidence: 99%
“…Economic use of cells, short experimental time, device scalability, low production and operation cost make it an attractive model for drug testing and a viable alternative to animal experimentation. The only other existing PAH-on-a-chip model 71 included intimal, medial and adventitial cells from PAH pulmonary arteries grown on polylysine-coated glass in straight channels arranged side-by-side, with cell-to-cell contact restricted to the gaps between silicone posts situated between the channels. This model can provide valuable information regarding paracrine regulation of cell migration (de ned as remodelling sic) but cannot evaluate endothelial barrier function and is limited by poor accessibility of patient lung material, which precludes its wider application in research and drug testing.…”
Section: Discussionmentioning
confidence: 99%
“…Microchip systems with micron-sized channels that permit cells to grow and interact with each other in a three-dimensional structure imitating the biological environment of tissues in the body have been used to bridge the gap between in vivo and in vitro systems [ 62 ]. In a recent publication, Al-Hilal et al from the Ahsan group used a microfluidic chip model simulating a PAH-insulted artery to study the sex discrepancy in PAH pathophysiology [ 63 ]. Chips composed of cells from male patients demonstrated decreased intimal (endothelial cells) but greater medial (smooth muscle cells) thickening compared to chips composed of cells from female patients [ 63 ].…”
Section: Sex Disparity In Pah and Microfluidic Chip Model Mimicking Pah-insulted Artery To Study Sex Discrepancy In Pah Pathophysiologymentioning
confidence: 99%
“…In a recent publication, Al-Hilal et al from the Ahsan group used a microfluidic chip model simulating a PAH-insulted artery to study the sex discrepancy in PAH pathophysiology [ 63 ]. Chips composed of cells from male patients demonstrated decreased intimal (endothelial cells) but greater medial (smooth muscle cells) thickening compared to chips composed of cells from female patients [ 63 ]. It is implicated that male patients develop a more severe disease compared to female patients illustrated by chips with male cells, exhibiting a higher number of PASMCs with a FSP-1 + CD31 − signature in the intimal and luminal layers [ 63 ].…”
Section: Sex Disparity In Pah and Microfluidic Chip Model Mimicking Pah-insulted Artery To Study Sex Discrepancy In Pah Pathophysiologymentioning
confidence: 99%
“…Similar concepts have been applied to other organ systems. Al-Hilal et al (2020) reported a pulmonary-arterialhypertension (PAH) model on a chip to elicit arterial remodeling under PAH. The authors fabricated a microfluidic device to emulate the luminal, intimal, medial, adventitial, and perivascular layers of a pulmonary artery.…”
Section: Disease Modelingmentioning
confidence: 99%